The Lost Princess of Oz - Baum, L. Frank (Lyman Frank), 1856-1919; Neill, John R. (John Rea), 1877-1943 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Lost Princess of Oz" by L. Frank Baum is a novel published in 1917. When Princess Ozma, ruler of Oz, mysteriously vanishes from her chambers, Dorothy and the Wizard organize search parties to find her. Meanwhile, powerful magic tools disappear from Glinda and the Wizard's collections. The quest leads Dorothy's group through strange communities and toward Ugu the Shoemaker, who may hold the answers. Can they recover the stolen magic and discover what happened to Ozma? (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Lost_Princess_of_Oz
Release date is 2008-01-30
E-text prepared by Chris Curnow, Joseph Cooper, Chuck Greif, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Oz (Imaginary place) -- Juvenile fiction; Fantasy literature; Friendship -- Juvenile fiction; Magic -- Juvenile fiction; Household employees -- Juvenile fiction; Princesses -- Juvenile fiction; Theft -- Juvenile fiction; Good and evil -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Gale, Dorothy (Fictitious character) -- Juvenile fiction; Princess Ozma (Fictitious character) -- Juvenile fiction; Wizard of Oz (Fictitious character) -- Juvenile fiction; Magicians -- Juvenile fiction